(untitled) (Journal of Society of Surgeons of Nepal, 2018)
Introduction: Computed tomography (CT) is the ‘gold standard’ for detecting subarachnoid hemorrhage (SAH) and digital subtraction angiography (DSA) for visualizing the vascular pathology. There is some correlation between the pattern (based on Fisher grading) and location of bleed on CT scan and eventual location of cerebral aneurysm(s). Our aim was to assess the correlation between distribution of hemorrhage on the initial CT scan and eventual site of the ruptured aneurysm at our institution. Methods: This retrospective review of prospectively collected data consisted of 50 patients with SAH over 8 months period. CT scan of patients performed within 72 hours after the ictus with suspected SAH were included in the study. Four neurosurgeons, who had at least three years of experience after being qualified, who were blind to the imaging studies, analyzed and scored independently the quantity and distribution of the hemorrhage on CT. Their prediction of the site of the ruptured aneurysm was recorded and this was correlated with the CT angiography (CTA) and/ or DSA findings. Results: Overall accuracy of prediction was 71.6 % (68.2-75%). Parenchymal cerebral hematoma was an excellent predictor for the site of a ruptured aneurysm but was present in only a few cases (16%). The next valid predictor was blood distribution on CT for ruptured anterior communicating artery (ACom) and middle cerebral artery (MCA) aneurysms (89.4% and 85% respectively). Pattern of blood on CT together with CTA/DSA findings was found to be reliable for identifying the ruptured aneurysm in patients with multiple aneurysms in all cases. Conclusion: The quantity and pattern of the blood on CT is a fairly reliable and quick tool for locating a ruptured MCA or ACom aneurysms. It is not, however, reliable for locating other ruptured aneurysms.